A low temperature bottom-up approach for the synthesis of few layered graphene nanosheets via C–C bond formation using a modified Ullmann reaction1. Issue 58 (25th June 2015) - Sawant, Sandesh Y.; Somani, Rajesh S.; Cho, Moo Hwan; Bajaj, Hari C.
<x xml:space="preserve">Abstract</x> A low temperature, single-pot, bottom-up approach for the synthesis of few layered graphene sheets using the modified Ullmann reaction is reported.